The Rights of Controlling State in Indonesia Against Land Tenure of Customary Law Community - Alpi Sahari (RIRAI Publisher, 2021)
In order to achieve public welfare as tasks and responsibilities delegated to the government in the administration of public welfare (bestuurzorg) including the land sector which includes, among others, regulation, implementation of authority to enforcement of land law. Implementation of bestuurzorg by the government is more oriented towards economic democracy so that ignoring the principle of justice for indigenous peoples in controlling land parcels. The method used in this paper is juridical normative by applying an approach to legal principles and a legal synchronization approach both vertically and horizontally to the State's right to control over land tenure by customary law communities. The results show that land tenure for customary law communities in the UUPA emphasizes as long as it still exists and does not conflict with national interests. This implies that there has been legal pluralism. The occurrence of weak legal pluralism in national land law is indicated by the enactment of UUPA and its various implementing regulations as positive law in the form of written state/national law, on the one hand and on the other hand customary law which is generally unwritten and applies specifically to each other. The applicable customary law in each region. Weak legal pluralism is one of the factors causing legal disputes in substantive settings, especially in land disputes over customary rights which affect their implementation in the field and cause injustice. legal pluralism and making UUPA the center of various land regulations (legal centralism), and is the only land rule that applies nationally (legal unification).